Tuberculosis en Rhea Americana y Gallus Sp. en cautiverio - Jorge, M.C. (2007)
Avian tuberculosis is worldwide distributed and affects domestic and wild birds. Aetiological agent is Mycobacterium avium subsp. avium. Its zoonotic potential has acquired importance since HIV pandemia, that is why the manipulation of viable microorganism should be done with careful biosecurity measures. Primary source of infection is the environment contaminated with these microbes. Clinical signs are not uniform and the confirmation of the disease is by bacteriologycal isolation. The purpose was to identify by histopathologycal, bacteriologycal and molecular biology methods the aetiology from tuberculosis like lesions found in an ornamental race of Gallus sp. (Japanese Silkie) and Rhea americana. At post-mortem examination granulomas were observed which presented in the histopathology caseonecrotized center with acid-fast bacili. M. avium subsp. avium was confirmed by bacteriology and PCR in cultured strains. These allowed to arrive to the aetiologycal diagnosis by the combination of methods and describe for the first time in Argentina tuberculosis in ratites.\n